STUDENTS' SCIENCE RELATED EXPERIENCES, INTEREST IN SCIENCE TOPICS AND THEIR I NTERRELATION SOME IMPLICATIONS - Gafoor, K. Abdul; Smitha Narayan (SCHOOL SCIENCE, 2010)
There are mounting evidences of decline in the interest of young people in pursuing science. The policy report of ninth meeting of Global Science Forum (2003) found that there is steady decline inthe number of students in science and technology. In India also, there isa similar trend of decline in interest to pursue study of science interest. National Science Survey (Shukla, 2005) has shown that interest in science as well as satisfaction with the quality of Science teaching declined as the age increased. One cannot take the decline in interest in science lightly. Surveys across the globe suggest that lack of interest in science is mainly due to science being less intrinsically motivating (Global Science Forum, 2003; National Science Survey, Shukla, 2005), nature of science being cutoff from real world and its content being overloaded with matters unrelated to the life of students (Hill and Wheeler, 1991; Osborne and Collins, 2001). One way of making science relevant is to base science on experiences in which pupils are interested and those that can find applications in real life.